1989
DOI: 10.1044/jshd.5401.74
|View full text |Cite
|
Sign up to set email alerts
|

Differentiating Alzheimer's Patients from the Normal Elderly and Stroke Patients with Aphasia

Abstract: The performance of individuals with mild and moderate Alzheimer's disease (AD), normal age-matched elderly individuals, and stroke patients with fluent and nonfluent aphasia were compared on a group of neuropsychological tasks. The unique performance profiles associated with each subject group are discussed, and the best tasks for intergroup differentiation specified. Whereas the tasks employed were efficacious for discriminating early- and middle-stage AD patients from normal subjects and aphasic stroke patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
1
2

Year Published

1991
1991
2016
2016

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(27 citation statements)
references
References 0 publications
0
24
1
2
Order By: Relevance
“…All participants scored 27 or better on the MMSE (mean: 29.6), above lower-quartile cutoff scores for healthy older adults (Bleecker, Bolla-Wilson, Kawas & Agnew, 1988). All participants also had a delayed:immediate recall ratio of .70 or better on the ABCD (mean: .97), above the reported scores for adults with dementia (Bayles, Boone, Tomoeda, Slauson & Kaszniak, 1989). Furthermore, all participants passed a 40dB pure-tone hearing screen (unaided) at 500, 1000, 2000, and 4000 Hz bilaterally.…”
Section: Studymentioning
confidence: 71%
“…All participants scored 27 or better on the MMSE (mean: 29.6), above lower-quartile cutoff scores for healthy older adults (Bleecker, Bolla-Wilson, Kawas & Agnew, 1988). All participants also had a delayed:immediate recall ratio of .70 or better on the ABCD (mean: .97), above the reported scores for adults with dementia (Bayles, Boone, Tomoeda, Slauson & Kaszniak, 1989). Furthermore, all participants passed a 40dB pure-tone hearing screen (unaided) at 500, 1000, 2000, and 4000 Hz bilaterally.…”
Section: Studymentioning
confidence: 71%
“…This ratio, which compares the amount of information recalled in an immediate condition compared to the amount of information recalled approximately 60 minutes later (delayed) is multiplied by 100 to yield the percentage remembered. Bayles et al [38] showed that normal elderly subjects (mean age = 70, SD = 7.25) will forget on average only *4% of the information that they immediately recalled, while mild dementia patients will forget *98%. All individuals enrolled had a delayed/immediate recall ratio that was greater than 95%.…”
Section: Methodsmentioning
confidence: 99%
“…The demarcation of linguistic deficits associated with APH versus primary cognitive impairments in AD is too simplistic. Clearly, linguistic deficits commonly appear as an early symptom of AD (Bayles et al 1989) and cognitive deficits are frequently documented in APH (Chapman and Ulatowska 1994). This study demonstrated that low language performance, on the standardized language measures, appears to be a sensitive predictor of failure on spontaneous proverb interpretations regardless of the diagnostic classification of either APH or AD.…”
Section: Discussionmentioning
confidence: 99%